A Politeness Language Study of Karampuang Culture in Sinjai, South Sulawesi - Andi Mulyani Kone; Rosmiaty Pammu; Wahdaniyah Jamal (Tamaddun Life, 2019)
The aims of this research is to explore and to represent the form and the characteristics of linguistic politeness, in buginese Karampuang Sinjai, South Sulawesi society. The method employed was descriptive method. The source of data divided into two categories, primary data will be collected and analyzed as an object of the people in Karampuang Sinjai. Secondary data that was some literature related to the object analyzed. The result of this research show the characteristics and the forms of linguistic politeness in Karampuang Sinjai, South Sulawesi.